Numerical study on the combustion process of a biogas spark-ignition engine - Carrera, José; Riesco, José; Martínez, Simón; Sánchez, Fausto; Gallegos, Armando (Vinča Institute of Nuclear Sciences, 2013)
The fuel called biogas is obtained through anaerobic digestion of different types of organic waste, providing a way to tap the energy stored in organic matter. The use of this fuel is also attractive from the standpoint of global warming because its ap- plication does not register a net emission of carbon dioxide into the atmosphere possible use for this fuel is to feed the spark-ignition internal combustion en- gines. In the present, there is little information available about the process of com- bustion in internal combustion engines fueled by biogas. The combustion process of by biogas is characterized in terms tion of combustion, i. e., depending on the time elapsed while the reac- an of the dura tants (methane and oxygen) are transformed into products (mainly carbon dioxide and water). This study numerically evaluates the way in which the geometrical pa- rameters such as the compression ratio and operating parameters like engine speed, the excess air, the time of spark timing and carbon dioxide content of biogas affect the evolhution of the combustion process. To carry out this study, a five factors and trwo levels experiment was designed and conducted, based on which, the most influential parameters were identified. Equations expressing the combustion char- acteristic parameters, as a function of the geometric and operation parameters of a spark ignited engines, are delivered as a result